Ethics of Ikram al-Dayf for Quality Muslim-Friendly Hospitality Services - Kamri, Nor 'Azzah; Sarif, Suhaili; Ali, Nor Aini; Abdul Mokti, Hawwa (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
The purpose of this article is to explore the concept of ikram al-dayf and its potential to be adapted into the Muslim-friendly tourism and hospitality practices. This article also introduces a set of ethical values for honoring guests in reference to the concept of ikram al-dayf. The concept of ikram al-dayf is pertinent to improve the Muslim-friendly staffs’ knowledge and understanding on how they should treat their guests better, since their service quality especially related to customer service aspect is still questionable. The article in the beginning presents the Muslim-friendly tourism and hospitality industry scenario and its related standards to show the needs for quality Muslim-friendly guest service. Next, it describes the established dimensions of service quality (SERVQUAL) model. Third, it explains the concept of ikram al-dayf and its relationship to guest service quality. It is based primarily on evidence from the Qur’an and the hadith. Fourth, it inserts ethical values based on the concept of ikram al-dayf into the dimensions of SERVQUAL. Finally, it briefly outlines the importance of applying ikram al-dayf ethics to be applied in Muslim-friendly hospitality practices. The article highlighted four core ethical values, namely qawlan karima, amanah, ta’ awun and ihsan which need to be given special attention for the best quality of service. These four ethical values suit the four dimensions of service quality and can be applied in the guest service phases (pre-arrival, arrival, stay, and departure of guests). The findings can then be embedded in the existing SERVQUAL dimensions as an added value for the use of Muslim-friendly hospitality players. The appreciation of ikram al-dayf ethics is not merely meant to portray the beauty of Islamic morality but also to improve service quality and achieve higher customer satisfaction. Eventually, it will be a competitive advantage for Muslim-friendly hospitality services to attract more customers especially among Muslims guests.